Relationship between Instructional Supervision and Teachers’ Job Satisfaction - Kumari, H. M. Lalitha (Researchparks Publishing, 2023)
The main purpose of this study was to find out the extent to which instructional supervision by internal supervisory teams’ was associated to teachers’’ job satisfaction. In order to achieve the purpose three specific objectives were guided; find out demographic characteristics of the secondary teachers, identify supervisory practices used by school internal supervisory teams particularly during the COVID 19 Pandemic and describe relationships between components of supervision and teachers’ job satisfaction. The study was carried out in association with three hundred sample units of secondary level teacher targeting to answer the research questions that were built. An online survey method was adopted in this study. A Google form questionnaire was used as data collection instruments. The data collected through the google form were presented by using percentages, tables and graphs, standard deviation and correlation coefficient. Results revealed that more than 78% percent of secondary level teachers’ instruction was not observed by their internal supervisory teams during year 2020 to 2021. In addition, a significant number of secondary level teachers (90%) had not participated in pre-observation conference and post observation conference with their supervisory teams. It was concluded that a significant number of secondary level teachers in Sri Lanka were neither supervised nor evaluated during COVID 19 Pandemic. Further, it was found that the most important components of supervision which included instructional observation, pre-observation conference and post-observation conference, assistance from supervisory teams in terms of lesson planning were not useful factors of secondary level teachers’ job satisfaction. It is, therefore, recommended that, the school principals must motivate their internal supervisory teams in order to adopt alternative methodologies such as online instructional supervisory approach particularly during a pandemic situation.